Total flight hours in the Australian Antarctic Territory (AAT) by Australian helicopters and fixed wing aircraft - PATE, ADRIAN (hasPrincipalInvestigator); PATE, ADRIAN (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION The number of helicopter and fixed wing hours flown and fuel consumed at Casey, Davis, Mawson, Macquarie Island stations and field locations are recorded by Station Leaders on a fortnightly basis and reported to Shipping and Air Operations (SAO). TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION Rotary and fixed wing aircraft are used for the resupply of stations and movement of personnel and equipment to and from remote field locations throughout the Australian Antarctic Territory (AAT). In addition, these aircraft are used for observation flights of animal populations and other aerial survey work. They also contribute towards the total level of emissions in the AAT. Changes in the quantity of hours used and fuel consumed provides an indication of sources of possible change to the level of emissions in the AAT. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Flights between stations, field sites and ships. Frequency: Annual report Measurement technique: Direct reading of flight logs and purchasing records. SAO staff records the data. RESEARCH ISSUES In the future, it is planned to automate the collection of most of this data. Furthermore, the measurement of aircraft fuel usage is the first step towards a more detailed monitoring of our air support operations. The end product will aim to plot geographically (location and elevation) the extent of our aircraft operations. This will not only record our presence in Antarctica, but also will help to validate our own stated policy on flight restrictions and our adherence to the policy. LINKS TO OTHER INDICATORS Station fuel usage; field trips; station person days; area protection and management; Incidents resulting in environmental impact.